Electrodeposition of Three‐Dimensional Network Nanostructure PEDOT/PANI for Simultaneous Voltammetric Detection of Ascorbic Acid, Dopamine and Uric Acid. Issue 4 (24th January 2020) - Wang, Qiangwei; Sun, Haobo; Liu, Qianrui; Li, Lianzhi; Kong, Jinming
Abstract: In this study, poly(3, 4‐ethylenedioxythiophene) (PEDOT) and polyaniline (PANI) were electrodeposited via cyclic voltammetry (CV) on glass carbon electrode (GCE) layer by layer. The prepared electrode (GCE/PEDOT/PANI) was used for the simultaneous sensitive determination of ascorbic acid (AA), dopamine (DA) and uric acid (UA) at different oxidation potentials. The peak distances of AA and DA, DA and UA, AA and UA were 216 mV, 104 mV, 320 mV, respectively. For individual detection of AA, DA and UA, the linear ranges were 1×10 −4 ‐1×10 −2  M, 3×10 −5 ‐1×10 −3  M and 7×10 −7 ‐1×10 −4  M with detection limits of 2.42×10 −5  M, 4.58×10 −6  M and 2.38×10 −7  M (S/N=3), respectively. For simultaneous detection of AA, DA, and UA, the linear response ranges were 1×10 −4 ‐1×10 −3  M, 3×10 −4 ‐1×10 −2  M, and 3×10 −6 ‐1×10 −4  M with detection limits of 6.91×10 −5  M, 3.66×10 −5  M and 4.13×10 −7  M (S/N=3), respectively. The GCE/PEDOT/PANI displayed good selectivity, reproducibility and storage stability, and was further applied to the detection of AA, DA, and UA in 5% normal human serum samples. Abstract : Three‐dimensional network structure PEDOT/PANI was electrodeposited on GCE; Ascorbic acid, dopamine and uric acid are oxidized on the surface of GCE/ PEDOT/PANI at different oxidation potentials.